A Structure-based Design Approach to Catharanthus roseus Phytoconstituents as Potential Inhibitors of B-Cell Lymphoma 6 Protein - Shahid Attar; Samiksha Bhor (International Journal of Bioinformatics and Computational Biology, 2023)
Objectives: Lymphoma is a cancerous disease. It develops into millions of people worldwide. Identify the naturally active compounds from Catharanthus roseus, they have multiple values in the medicinal field of Siddha, and Indian Ayurveda are used as a disease-preventing agent. Drug illness prediction, toxicity prediction, statistical information, molecular docking, as well as absorption, distribution, metabolism, and excretion (ADME) analysis are used to predict the fit ligand as a drug. Methods: The database of protein data bank (PDB) was used to retrieve the BCL6 protein and its chains after the purification. The poor binding affinity of ligands with target protein was removed, ADMET analysis and Swiss-ADME lab webserver were used for drug-likeness analysis, and molecular docking is done with the PyRx. Results: The dihedral angles Φ and ψ combination in the backbone of protein is shown in the Ramachandran plot analysis. The five compounds of C. roseus have a potential binding affinity with BCL6 found in molecular docking. ADMET profile and docking interaction showed five compounds Perivine, Alstonine, Quercetin, 16-Methoxytabersonine, and Vindolininol are possess the properties of the drug and safe to use. Conclusion: The previous and present studies suggest that Perivine, Alstonine, Quercetin, 16-Methoxytabersonine, and Vindolininol could inhibit the chain A, B, and C of BCL6 protein and have significant affinity binding. The therapeutic strategies against B-cell lymphoma interpreted based on molecular binding and interaction
Keywords: ADMET analysis; Auto-docking; B-cell lymphoma; BCL6; Cancer; Catharanthus roseus; Phytocompound